EDUKASI DAN PELAKSANAAN SENAM HIPERTENSI UNTUK MENGONTROL TEKANAN DARAH SEBAGAI UPAYA PENCEGAHAN STROKE PADA LANSIA - Anna Sarifah; Arista Putri Aryanti; Athaya Zuhra Silanurrahmi; Azka Arsyada Hafizha; Berlian Kasih Kurniawati; Berlian Nabiilah Luthfriyadi; Muhammad Hammam Izzuddin; Safrida Aulia Nadyasari; Dita Mirawati (CV. Denasya Smart Publisher, 2026)
Hypertension is a non-communicable disease commonly experienced by older adults and is one of the leading risk factors for stroke. This condition is frequently found among the elderly due to physiological changes associated with aging as well as unhealthy lifestyle habits. The low level of knowledge among older adults regarding hypertension, its risk factors, and the importance of physical activity contributes to suboptimal blood pressure control in this population. This community service program aimed to improve the knowledge of older adults about hypertension and to promote the implementation of physical activity through health education and hypertension exercise programs. The activity was conducted at Posyandu Lansia Melati VIII in Gatak Village, Sukoharjo Regency, involving 27 elderly participants. The methods used included health education through video and presentation media, direct practice of hypertension exercises, and knowledge evaluation using pre-test and post-test assessments. The results showed a significant increase in participants’ knowledge, from 55.6% of participants who previously lacked understanding of hypertension to 92.6% who demonstrated adequate understanding after the educational intervention. In addition, participants showed high enthusiasm in participating in hypertension exercise sessions regularly with community health volunteers